The effects of endoparasitism on the productivity of sheep in the Coast of Kenya - Reynolds, L. (International Livestock Centre for Africa, 1991)
This paper describes the study area and give some figures on the losses due to internal parasites. It presents previous studies on the effect of parasitism on small ruminant productivity. It summarises results from ILCA's preliminary investigations in the coast of Kenya and outlines future work.